Being Positive. Approaching Career Design from the Perspective of Positive Psychology - Klimka, Małgorzata; Budzińska, Grażyna (Journal of Education Culture and Society, 2020)
Constructing a career path based upon positive personal potential and positive individual resources is a significant factor for professional development of employees and their success on today’s labour market. A satisfying career, an inherent element of personal well-being and good life, is linked with an ability to explore and reinforce signature strengths. In order to effectively design programmes which could support young people who are preparing to enter a job market, it is essential to acquire knowledge about values and character strengths and their perceptions among young people living in Poland and abroad. The article presents comparative analysis of signature strengths perceptions among young people in different cultures and discusses the significance of the most striking differences.